Characterization of The Oncogeriatric Population Attended at the Arturo López Perez Foundation (Falp) Cancer Institute - Soto, Ruben; Quilodran, Rocio; Najera, Manuel; Ferrer, Pedro (Journal of Hematology and Oncology Research, 2022)
This study characterizes an oncogeriatric cohort at a cancer institute, reporting tumor types, comorbidities, geriatric assessments, and treatment patterns. Findings inform service planning and individualized care for older adults with cancer.
Keywords: Non-communicable diseases; cardiovascular diseases; cancer